Experimental investigations of the needle winding technology regarding the influence of the wire guide geometry on the tensile wire force - Stenzel, P.; Dollinger, P.; Richnow, J.; Franke, Jörg; Endisch, C.; et al. (Proceedings of the IEEE International Conference on Industrial Technology, 2015)
The needle winding technology is distinguished by a high degree of flexibility and automation. However, high wire tension due to the tensile winding force proves to be detrimental. Wire stress can cause an increase of the ohmic winding resistance, thus leading to a decrease of the degree of efficiency and a reduction of the continuous power of an electric machine. A closed-loop-control of the tensile winding force is basically possible, however, the influence of the wire guide on the tensile force cannot be included due to the possible measuring positions. In order to use the automation potential of the needle winding technology it has to be ensured that quality and power of the winding products are not degraded. Therefore the influence of the tensile winding force on ohmic resistance as well as the influence of the geometry of the wire guide on the tensile force has to be known. However, such investigations have either not been conducted so far or are currently not publicly accessible. The winding parameters are usually based on experience, which is not sufficient for high power density applications. Therefore, in this paper experimental investigations are presented concerning the above mentioned topics and potentials for improvement are identified.
CRIS-Team Scopus Importer:2023-03-07